THE DEVELOPMENT OF PROJECT-BASED LEARNING E-BOOK: A CASE STUDY FROM ACCOUNTING BILINGUAL CLASSES IN INDONESIA - Kartikasari, Nungki; Hudaya, Robith; Rizki, Novia; Hanani, Tri (Jurnal RAK (Riset Akuntansi Keuangan), 2023)
This article aims to develop an e-book based on Project Based Learning needs in the Basic Accounting course for Bilingual Classes. The type of research used is research and development. The research model used in this study is the modified ADDIE method, which consists of 5 stages: analyzing, designing, developing, evaluating, and implementing. The data collection in this research includes collecting material from credible sources, then arranging it according to the order of the material in the Semester Learning Plan, and using an attractive design. Design validation is carried out by media experts and material experts. The validation results show a good value where this e-book is suitable for use. Design revisions are only limited to minor revisions and these revisions are based on validation forms from media experts and material experts, such as consistent use of terms, additional discussions, and additional report examples. Small group trials have also been carried out and found that the basic accounting electronic book value is suitable for use.